PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN TEKS INFORMASI MENGGUNAKAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) DI KELAS V SDN 01 III KOTO RAMBATAN - Darapati, Dwinda; Yenti, Yesni; Elfia Sukma; Nur Azmi Alwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low ability of fifth-grade students at SDN 01 III Koto Rambatan, Tanah Datar Regency, in comprehending informational texts. Out of 18 students, only 7 (38.9%) achieved the KKTP with an average score of 60. This study aimed to describe the teaching module, the implementation of learning, and the improvement of informational text reading comprehension skills using the CIRC model. This classroom action research used the Kemmis and McTaggart model with the subjects being the teacher and 18 fifth-grade students, conducted in two cycles. Research instruments included teaching module observation sheets, teacher and student activity observation sheets, and learning outcome tests. The results showed improvements in all aspects: teaching module quality from 84.37% to 100%; teacher activity from 78.12% to 100%; student activity from 78.12% to 96.87%; average knowledge score from 60 to 82.6 with 100% mastery; In conclusion, the CIRC model effectively improves the informational text reading comprehension skills of fifth-grade elementary school students.